The evil fairy queen [videorecording (DVD)] - Wrench, James; Czartoryski, Julia; Sudbery, Kitty; Spendlove, Martyn; Leyland, Aniela; Tcherniak, Judy; Harris, Hannah (Actor); Mcelduff, Megan; Hunter, Luke, 1994-; Killip, Natasha (Vision Films, 2024)
Lured to a beautiful but remote farmhouse by a deceitful relative, a family decides to move in. Little do they know it's in the middle of a dying kingdom of fairies and the only way for them to rejuvenate their life force is by sacrificing their young daughter. As she is baited to the fairies' lair, her mother must fight to return her to safety and bring an end to the evil fairy queen's reign.